Interregional competition in the biorefinery industry - Clarke, Nathan (Kansas State University, 2013)
A major story in the recent history of US agriculture is the evolution and growth of the ethanol industry. A crucial factor in the profitability of an ethanol plant is the choice of its fixed location, as this has implications in the transportation costs associated with the acquisition of grain and sale of distiller’s grains. When the industry was in its infancy, where to locate, often, was based on strictly local factors. Primary considerations were local availability of grain and producer and community investment interests. Today, the ethanol industry is more mature and consolidated. As such, investment criteria have broadened from a localized to a total systems perspective. The focus of this study was to analyze construction, abandonment, and expansion of plant locations in ethanol producing regions, and the effects of regional transportation costs on the geographic growth of the industry. Comparison to previous research provided the basis to evaluate industry change. Current ethanol plant locations and their capacities were complied and compared with earlier data to identify plant exits, expansions and new construction. Aggregating those plant capacities by USDA crop reporting districts, feedstock consumption by biorefineries were calculated by crop reporting district, as was livestock feed demand from livestock numbers. Those data along with coarse grain production by crop reporting district were used to calculate excess feedgrain demand (supply) by region. Those regional data were used to construct linear programming network-flow models for the transportation of feedstock and for DDGS, respectively. Two models were used; the first was used minimize the interregional cost to transport feedstocks from excess supply regions to excess demand regions. The second was used to minimize the interregional cost to transport DDGS from excess supply regions to excess demand regions. These regional transportation costs were combined to find the total interregional transport by crop reporting district. Differences in such interregional transport costs affect the competitiveness of plants across crop reporting districts and should affect the strategic position of each plant location. Current plant locations and transportation cost results were compared with those from previous research and, with additional consideration to changes in production factors, provided further understanding of the recent growth and development of the ethanol industry.
Keywords: Biorefinery competition; Dried distillers' grains movements; Economics, Agricultural (0503)